Effects of core grain orientation on the mechanical properties of wood sandwich composite (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Utilization of sandwich composite during recent year has been driven by the fact that compositematerial has ultimately high strength and stiffness by weight than any other materials. The skins ofsandwich composites technically bear most of the applied loads, however, the core materials alsoplay an important role as it functions in providing continuous support to resist the shear stress.Hence, proper selection of core materials is required to establish a sturdy sandwich compositestructure. This paper presents an experimental investigation on the sandwich structure consists offibreglass/epoxy face skins and a mahang wood core. Sandwich composite with core grain orientedin parallel and perpendicular to the flat plane direction were tested for mechanical performance intension, compression and flexure. The results indicate that sandwich composite with grain orientedin parallel direction performed better in tensile properties with strength of 201.98 MPa whereassandwich composite with perpendicular core grain produced a higher value of compressionproperties with strength of 70.11 MPa. However, no significant effect of grain orientation wasobserved in flexural strength. The strength of sandwich composite is dependent on the grainalignment of the wood core as it functions exclusively as mechanical supporting cells to supportthe wood structure.
Keywords: mahang wood; fiberglass; epoxy; wood grain